2022
DOI: 10.3390/ijms24010488
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic, Structural and Functional Evolution of the LHC Gene Family in Plant Species

Abstract: Light-harvesting chlorophyll a/b-binding (LHC) superfamily proteins play a vital role in photosynthesis. Although the physiological and biochemical functions of LHC genes have been well-characterized, the structural evolution and functional differentiation of the products need to be further studied. In this paper, we report the genome-wide identification and phylogenetic analysis of LHC genes in photosynthetic organisms. A total of 1222 non-redundant members of the LHC family were identified from 42 species. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Compared to the control, our result showed that all genes were down-regulated after the waterlogging stress except for FEDA, which was consistent with the RNA-seq data (Figure 7). Lhca and Lhcb belong to light-harvesting chlorophyll a/b binding (LHC) superfamily, which plays critical roles in photosynthesis [30]. The expression change of Lhcb gene family normally influenced plant growth and development under abiotic stress [31].…”
Section: Validation Of Photosynthesis-related Genes Expression With Q...mentioning
confidence: 99%
“…Compared to the control, our result showed that all genes were down-regulated after the waterlogging stress except for FEDA, which was consistent with the RNA-seq data (Figure 7). Lhca and Lhcb belong to light-harvesting chlorophyll a/b binding (LHC) superfamily, which plays critical roles in photosynthesis [30]. The expression change of Lhcb gene family normally influenced plant growth and development under abiotic stress [31].…”
Section: Validation Of Photosynthesis-related Genes Expression With Q...mentioning
confidence: 99%